A neonate with intrauterine growth restriction and pseudo‐Bartter syndrome due to severe maternal eating disorder: A case report. Issue 12 (6th August 2020) - Babatseva, Evgeniya; Chatziioannidis, Ilias; Tagaraki, Alexia ‐ Angeliki; Tramma, Despoina; Dampala, Kalliopi; Chatzitoliou, Efthymia; Papacharalambous, Efthymia; Mitsiakos, Georgios; Tsakalidis, Christos; Karagianni, Paraskevi; Lithoxopoulou, Maria; Anastasiadis, Kleanthis; et al.
Abstract: Maternal diet before and during pregnancy plays an important role for the developing fetus. Any eating disorder in this period can cause transient or/and permanent negative effects on the mother and her offspring. Abstract : Maternal diet before and during pregnancy plays an important role for the developing fetus. Any eating disorder in this period can cause transient or/and permanent negative effects on the mother and her offspring.